Erythroblastic Island Macrophages Shape Normal Erythropoiesis and Drive Associated Disorders in Erythroid Hematopoietic Diseases - Li, Wei; Guo, Rongqun; Song, Yongping; Jiang, Zhongxing (Frontiers in Cell and Developmental Biology, 2021)
Erythroblastic islands (EBIs), discovered more than 60 years ago, are specialized microenvironments for erythropoiesis. This island consists of a central macrophage with surrounding developing erythroid cells. EBI macrophages have received intense interest in the verifications of the supporting erythropoiesis hypothesis. Most of these investigations have focused on the identification and functional analyses of EBI macrophages, yielding significant progresses in identifying and isolating EBI macrophages, as well as verifying the potential roles of EBI macrophages in erythropoiesis. EBI macrophages express erythropoietin receptor (Epor) both in mouse and human, and Epo acts on both erythroid cells and EBI macrophages simultaneously in the niche, thereby promoting erythropoiesis. Impaired Epor signaling in splenic niche macrophages significantly inhibit the differentiation of stress erythroid progenitors. Moreover, accumulating evidence suggests that EBI macrophage dysfunction may lead to certain erythroid hematological disorders. In this review, the heterogeneity, identification, and functions of EBI macrophages during erythropoiesis under both steady-state and stress conditions are outlined. By reviewing the historical data, we discuss the influence of EBI macrophages on erythroid hematopoietic disorders and propose a new hypothesis that erythroid hematopoietic disorders are driven by EBI macrophages.